Penguatan Penegakan Hukum Terhadap Kejahatan Bisnis dalam Skema Fraud Korporasi dan Penyalahgunaan Aset Perusahaan - Pudjianto Gondosasmito; Aida Ardini (JUNCTO: Jurnal Ilmiah Hukum, 2026)
This study aims to analyze the strengthening of law enforcement against business crimes in corporate fraud schemes and the misappropriation of company assets. This research employs normative legal research using statutory and conceptual approaches. Legal materials are analyzed qualitatively through grammatical, systematic, and conceptual interpretation. The findings show that company asset misappropriation is a common form of corporate fraud, occurring through cash embezzlement, inventory manipulation, misuse of company facilities, and irregularities in goods and services procurement. Law enforcement already has a normative basis through the Criminal Code, the Limited Liability Company Law, and Supreme Court Regulation Number 13 of 2016. However, its effectiveness is still constrained by complex corporate structures, evidentiary difficulties, limited capacity of law enforcement officials, and weak internal supervision systems. Therefore, stronger law enforcement must be integrated with preventive mechanisms through Good Corporate Governance, internal control, legal compliance culture, whistleblowing systems, and monitoring technology to create transparent, accountable, and high-integrity corporations.